Analysis of AI Precision Education Strategy for Small Private Online Courses - Lin, Yu-Shan; Lai, Ying-Hsun (Frontiers in Psychology, 2021)
In recent years, the learning efficacy of online to offline (O2O) teaching methods seems to outperform traditional teaching methods in the field of education. Students can use a small private online course (SPOC) teaching platform to preview class-related materials, learn basic knowledge, and enhance the practical experience of system development in offline courses. The research team applied an artificial intelligence (AI) precision education strategy to design a teaching experiment that evaluated whether this approach may lead to better learning outcomes. In addition to questionnaire surveys to ascertain students’ attitudes toward and their satisfaction with learning, this study employed in-depth interviews to understand a potential influence on changes in teachers’ curriculum design and teaching approaches when SPOCs was integrated into the traditional university classroom, as well as the impact of the AI precision education model. The results showed that the AI precision education model may facilitate students’ learning experience and enhance student achievement.